2014
DOI: 10.1016/j.freeradbiomed.2013.11.025
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondria-targeted mass spectrometry probe to detect glyoxals: implications for diabetes

Abstract: The glycation of protein and nucleic acids that occurs as a consequence of hyperglycemia disrupts cell function and contributes to many pathologies, including those associated with diabetes and aging. Intracellular glycation occurs after the generation of the reactive 1,2-dicarbonyls methylglyoxal and glyoxal, and disruption of mitochondrial function is associated with hyperglycemia. However, the contribution of these reactive dicarbonyls to mitochondrial damage in pathology is unclear owing to uncertainties a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 53 publications
2
46
0
2
Order By: Relevance
“…337 To evaluate the importance of dicarbonyl-related glycation processes to mitochondrial function, a mitochondria-targeted mass spectrometry probe for glyoxals, MitoG (Chart 48), was developed by linking the TPP + cation with alkoxy-substituted o-phenylenediamine. 338 …”
Section: Mitochondria-targeted Probes and Sensors For Reactive Oxymentioning
confidence: 99%
See 2 more Smart Citations
“…337 To evaluate the importance of dicarbonyl-related glycation processes to mitochondrial function, a mitochondria-targeted mass spectrometry probe for glyoxals, MitoG (Chart 48), was developed by linking the TPP + cation with alkoxy-substituted o-phenylenediamine. 338 …”
Section: Mitochondria-targeted Probes and Sensors For Reactive Oxymentioning
confidence: 99%
“…338 The MitoG probe can be used to determine relative mitochondrial levels of methylglyoxal and glyoxal under hyperglycemia. 338 Although the proposed methodology of dicarbonyl detection reports on mitochondrial glyoxal and methylglyoxal exposure, it cannot indicate the source of those dicarbonyls, as they may be produced in the cytosol with subsequent diffusion into mitochondria. The MitoG probe was used to assess the changes in glyoxal and methylglyoxal production in a mouse model of type I diabetes.…”
Section: Mitochondria-targeted Probes and Sensors For Reactive Oxymentioning
confidence: 99%
See 1 more Smart Citation
“…MitoB was also applied to mammalian systems and it was found that an intravenous injection of MitoB into a mouse enabled sufficient MitoB to be taken up into the heart to assess changes in mitochondrial ROS production during IR injury [37]. Therefore, MitoB can be used as a probe to assess mitochondrial hydrogen peroxide production in vivo , through generation of MitoP as an exomarker, and many other experimental models are currently being interrogated using MitoB and new types of probe designed to assess other aspects of mitochondrial function are also being investigated [3840]. …”
Section: Targeting Mass Spectrometric Ros Probes To Mitochondriamentioning
confidence: 99%
“…[62][63][64] The best understood of these targeting molecules is the triphenylphosphonium (TPP+) group which can be coupled to a broad range of pharmacophores and redox-sensitive probes. [16,65,66] These molecules have been used both in vivo and in cell culture to probe the mechanisms of redox signaling, and the effects they elicit are generally ascribed to the properties of the functional group and not the carrying molecule. However, it was recently shown that the TPP + group itself can modulate mitochondrial bioenergetics and the effects vary with the linker group used to attach the functional pharmacophore.…”
Section: Mechanisms Of Mitochondrial Reactive Oxygen Species and Thermentioning
confidence: 99%